2020
DOI: 10.1071/ah18155
|View full text |Cite
|
Sign up to set email alerts
|

Depression, suicide risk, and workplace bullying: a comparative study of fly-in, fly-out and residential resource workers in Australia

Abstract: Objectives The primary objective of this study was to establish whether clinical depression and increased suicide risk differed between Australian fly-in, fly-out (FIFO) workers and their residential counterparts in the resources sector. We also sought to identify whether bullying and social support were associated with depression and suicide risk in this cohort. Methods A cross-sectional survey design was used. Completed questionnaires were received from 751 respondents who were employed in the Australian r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…The majority of participants in the studies were men (averagely 91.2%), and all were aged between 16 and 68 years (mean of study means=39.23±4.29 years). The majority (89.25%) of studies were rated medium to high on the JBI Quality Rating Scale: 58 of 90 studies, for example, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] rated ≥70% (high), 23 studies, for example, 18 44-49 rated 50%-69% (medium), and 9 studies, for example, 17 50-57 rated <50% (low) (table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…The majority of participants in the studies were men (averagely 91.2%), and all were aged between 16 and 68 years (mean of study means=39.23±4.29 years). The majority (89.25%) of studies were rated medium to high on the JBI Quality Rating Scale: 58 of 90 studies, for example, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] rated ≥70% (high), 23 studies, for example, 18 44-49 rated 50%-69% (medium), and 9 studies, for example, 17 50-57 rated <50% (low) (table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Bullying has even been linked to symptoms consistent with post-traumatic stress syndrome-type symptoms, as well as suicidal thoughts and attempts. Indeed, there is evidence that some victims of bullying do in fact end up committing suicide (Mikkelsen & Einarsen, 2001 ; Miller et al, 2019 ; C. Rayner et al, 2002 ). As Davenport et al, ( 1999 , p. 33) suggest, “for the victim, death –through illness or suicide –may be the final chapter in the mobbing [bullying] story.”…”
Section: Introductionmentioning
confidence: 99%
“…Researches showed that problems such as sleep disorders (Lallukka, Rahkonen & Lahelma, 2011), high levels of anxiety (Rodríguez-Muñoz, Moreno-Jiménez & Sanz-Vergel, 2015), difficulty in concentration (Einarsen & Mikkelsen, 2003), lower self-esteem and selfefficiency (Chang, Su, & Mizanur, 2018;Hsieh, Wang, & Ma, 2019), burn out (Livne & Goussinsky, 2018;Purpora et al, 2019), post-trauma stress disorder (Matthiesen & Einarsen, 2004), depression (Chang, Su, & Mizanur, 2018;Miller et al, 2019), psychosomatic health problems (Björkqvist et al, 1994), physical problems (Ciby & Raya, 2018;Lever et al, 2019) are observed as consequences of workplace bullying related employees' reactions. Furthermore, O'Moore and colleagues (1998) pointed out that workplace bullying not only influences physical and mental health of employees but also damages the careers of victims.…”
Section: Resultsmentioning
confidence: 99%